Salmon welfare index model 2.0: an extended model for overall welfare assessment of caged Atlantic salmon, based on a review of selected welfare indicators and intended for fish health professionals - Jostein M. Pettersen; Marc B.M. Bracke; Paul J. Midtlyng; Ole Folkedal; Lars H. Stien; Håvard Steffenak; Tore S. Kristiansen (Reviews in Aquaculture, 2014)
Here, we present an extended version of a semantic model for overall welfare assessment of Atlantic salmon reared in sea cages. The model, called SWIM 2.0, is designed to enable fish health professionals to make a formal and standardized assessment of fish welfare using a set of reviewed welfare indicators. SWIM 2.0 supplements SWIM 1.0, which was designed for application by fish farmers. We searched the literature for documented welfare indicators that could be used by fish health professionals. The selected indicators are eyes, cardiac condition, abdominal organs, gills, opercula, skeletal muscles, vaccine‐related pathology, aberrant fish, necropsy of the dead fish and active euthanasia. Selection criteria for the SWIM 2.0 indicators were that they should be practical and measureable on salmon farms by fish health professionals and that each indicator could be divided into levels from good to poor welfare backed up by relevant scientific literature. To estimate each indicator's relative impact on welfare, all the indicators were weighted based on their respective literature reviews and according to weighting factors defined as part of the semantic modelling framework. This was ultimately amalgamated into an overall SWIM 2.0 model that can be used to calculate welfare indexes for salmon in sea cages, taking into account the available fish health expertise. Using this model, an example calculation based on recordings and samplings done from an Atlantic salmon sea cage containing 106 000 fish yielded an overall welfare index of 0.81 of a maximum of 1.0.